228k views
0 votes
4x + (-3) = 5x + 3?????

User Nejcs
by
5.1k points

2 Answers

4 votes

Answer:


x=-6

Explanation:

Isolate the variable.


4x+(-3)=5x+3


4x=5x+6


0=x+6


x=-6

Hope this helps!

User Denkweite
by
4.3k points
7 votes

Hi there! :)


\large\boxed{x = -6}

Solve for x:

4x + (-3) = 5x + 3

Adding a negative number is simply subtracting, therefore:

4x - 3 = 5x + 3

Subtract 4x from both sides:

4x - 4x - 3 = 5x - 4x + 3

-3 = x + 3

Subtract 3 from both sides:

-3 - 3 = x + 3 - 3

-6 = x

User Uselpa
by
5.9k points